A scoping review of evaluation frameworks and their applicability to real-world physical activity and dietary change programme evaluation - Judith F. Fynn; Wendy Hardeman; Karen Milton; Andy P. Jones (BMC, 2020)
Abstract Background Physical activity and dietary change programmes play a central role in addressing public health priorities. Programme evaluation contributes to the evidence-base about these programmes; and helps justify and inform policy, programme and funding decisions. A range of evaluation frameworks have been published, but there is uncertainty about their usability and applicability to different programmes and evaluation objectives, and the extent to which they are appropriate for practitioner-led or researcher-led evaluation. This review appraises the frameworks that may be applicable to evaluation of physical activity and/or dietary change programmes, and develops a typology of the frameworks to help guide decision making by practitioners, commissioners and evaluators. Methods A scoping review approach was used. This included a systematic search and consultation with evaluation experts to identify evaluation frameworks and to develop a set of evaluation components to appraise them. Data related to each framework's general characteristics and components were extracted. This was used to construct a typology of the frameworks based on their intended programme type, evaluation objective and format. Each framework was then mapped against the evaluation components to generate an overview of the guidance included within each framework. Results The review identified 71 frameworks. These were described variously in terms of purpose, content, or applicability to different programme contexts. The mapping of frameworks highlighted areas of overlap and strengths and limitations in the available guidance. Gaps within the frameworks which may warrant further development included guidance on participatory approaches, non-health and unanticipated outcomes, wider contextual and implementation factors, and sustainability. Conclusions Our typology and mapping signpost to frameworks where guidance on specific components can be found, where there is overlap, and where there are gaps in the guidance. Practitioners and evaluators can use these to identify, agree upon and apply appropriate frameworks. Researchers can use them to identify evaluation components where there is already guidance available and where further development may be useful. This should help focus research efforts where it is most needed and promote the uptake and use of evaluation frameworks in practice to improve the quality of evaluation and reporting.